EDUKASI TENTANG ANEMIA PADA SANRTIWATI PONPES ZIENTA ELHARAM BARACA - Nurmayani, Winda; Elisa Oktaviana (Jurnal LENTERA, 2025)
Health education about anemia needs to be conducted because cases of anemia among adolescents continue to occur. The adolescent phase is a time that is vulnerable to health risks because during this phase, there is rapid body development that requires adequate nutritional sources. However, these nutritional needs are often neglected by adolescents, which can lead to various health problems, such as the incidence of anemia among teenagers. Adolescent girls are also a population that has a higher risk of anemia compared to boys, because during this time adolescent girls experience menstruation and have a desire to stay slim, leading them to diet and reduce food intake, which affects their nutritional fulfillment. Objective: to increase the knowledge of female students about anemia. Method: This activity is carried out in three stages, starting with preparation, followed by implementation, and finally evaluation. This community service activity was held on November 10, 2024, at the Zienta Elharam Baraca Islamic Boarding School. The event was attended by 27 female students. The delivery of the material was done through lectures using media such as projectors, followed by the distribution of leaflets to the students. Evaluation was conducted by providing a questionnaire regarding anemia consisting of 10 multiple-choice questions, where answering correctly scored 2 points and answering incorrectly scored 1 point. The evaluation activity was conducted twice, before and after the education. Results: there was an effect on the level of knowledge of the students before and after the education with a p-value of 0.000. This indicates that the counseling was successful. Suggestions: It is hoped that there will be continuous counseling activities with different themes related to health.ane